Peningkatan Kapasitas Digester Untuk Kecukupan Produksi Biogas Sebagai Bahan Bakar Generator Listrik - Rudianto, Rudianto; Zulhamidi, Zulhamidi; Edwar, Ester; Pharmayeni, Pharmayeni; Ekawati, Irna; Putri, Gustiarini Rika (Journal of Industrial Community Empowerment, 2024)
The development of dairy farming in Nagari Lasi District Canduang, Agam Regency, West Sumatra Province, has provided the materials a massive source of biogas production. The number of cattle in Nagari Lasi has reached around 1000 heads, plus other livestock such as Buffaloes and Goats. The manufacture of digesters in the previous year's Community service activities was a success. It produces biogas and is used for cheese production and household supply. However, the amount of biogas produced is still tiny. To realize "Community-Independent Energy," power generator installation is necessary. The biogas supply must be in large quantities and available continuously for the generator to operate. Biogas currently produced by the digester is insufficient to produce the biogas required by the generator. Therefore, biogas production capacity needs to be improved by expanding the volume of the digester that will be processing cow dung into biogas. Increasing digester capacity has significantly increased biogas production, reaching 12 m3 per day. This amount is enough to be used as fuel for an electric generator continuously.